The Influence of The Internal Control System, Follow-up Recommendations, and Regional Characteristics on Audit Opinion - Khabibah, Nurul; Aryati, Titik (Jurnal Indonesia Sosial Sains, 2024)
This research analyzes the influence of the internal control system (SPI), follow-up recommendations, and regional characteristics on audit opinions. The regional characteristic variables used are regional size and level of prosperity. Hypothesis testing was carried out using the binary logistic regression analysis method with the help of SPSS software. The population in this study is all district governments in Indonesia. The purposive sampling method selected the research sample with a total sample of 270 districts. The study results show that the internal control system negatively affects audit opinions. The follow-up of recommendations and regional sizes positively affect audit opinions. The level of prosperity did not affect the audit opinion. The results of this study show the importance of effective and efficient implementation of SPI, fulfillment of follow-up recommendations, and accountable financial reporting. Further research is suggested to add variables that affect audit opinions and use a sample of all local governments to assess audit opinions more accurately.